Một số điểm tương đồng giữa sử thi Xơ Đăng và sử thi Bahnar - Lê, Ngọc Bính - Nguyễn, Ngọc Chiến (2023)
The epics told by two ethnic groups, the Xo Dang and the Bahnar, belong to the Central Highlands epic region and have similarities in content and form. This article introduces some basic general features of the Xo Dang and Bahnar epics in terms of theme, plotline, and characterization, and analyzes the cause and meaning of the similarities. We use comparative, interdisciplinary research methods to clarify the similarities in the epic art of the two ethnic groups, thereby showing the unity in the diversity of the epic region of the Central Highlands.